Application of Inquiry Learning Method in English Language Learning - Dewi, Dita Lutfiah Puspa; Putri, Egiska Lusita; Ameliana, Sisil; Putri, Yeyen Meyzha; Sucitra, Diah Ayu (JURNAL MANAJEMEN MUTU PENDIDIKAN, 2024)
The purpose of this article review is to analysis the role of inquiry learning models in English learning outcomes. In this study, the researcher applied the inquiry learning model with the literature review method of journals from the last five years as the research orientation to determine the effectiveness of the learning model in improving the quality of students' English learning at school. The data used in this study are national scientific articles from 2018 to 2023. The author identified 17 articles and selected seven of them for analysis. The results of the literature study show that the inquiry learning model has a significant impact on improving English language learning outcomes in schools. The effect of inquiry learning can be seen in the learners' improvement in English comprehension.Keywords: English language, learning outcomes, Inquiry learningDOI: 10.23960/jmmp .v12.i1.2024.05